Synthesis and characterization of zinc sulfide nanoparticles loaded on activated carbon for the removal of methylene blue. Issue 3 (27th June 2012) - Ghaedi, M.; Larki, H. Abbasi; Kokhdan, S. Nasiri; Marahel, F.; Sahraei, R.; Daneshfar, A.; Purkait, M.K.
<x xml:space="preserve">Abstract</x> In the first part of this research, zinc sulfide nanoparticle loaded activated carbon was synthesized by a simple and low cost procedure. Zinc sulfide nanoparticles were prepared, characterized and loaded on commercially available activated carbon. The zinc sulfide nanoparticle was characterized by UV–vis, SEM and XRD analysis. The objective of this study was to assess the suitability and efficiency of zinc sulfide nanoparticle loaded activated carbon (ZnS‐NP‐AC) for the removal of Methylene blue (MB) from aqueous solution. Adsorption studies were conducted in a batch mode and the influences of various operating parameters including pH, contact time, initial dye concentration, ZnS‐NP‐AC amount on the extent of MB adsorption were investigated in details. The adsorption equilibrium data were fitted well to the Langmuir model. The maximum MB adsorption capacity was found as 100 mg g−1 of adsorbent. To investigate the kinetic of adsorption, the time dependency of removal percentage of MB on ZnS‐NP‐AC was analyzed by various models such as, pseudo‐first‐order, pseudo‐second‐order, Elovich, and intraparticle diffusion kinetic. It was found that the adsorption follows pseudo‐second‐order kinetic with involvement of intraparticle model. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 535–542, 2013